Phosphorus use efficiency of Trifolium subterraneum as affected by seeding rate under rainfed conditions - Stefanou P.; Kyriazopoulos A.P.; Abraham E.M.; Katsinikas D.; Parissi Z.M.; Manousidis T.; Koutroubas S.; Orfanoudakis M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Legumes are particularly important feed sources for livestock due to their high nutritive value. The objective of this study was to examine the agronomic phosphorus use efficiency (PUE) of Trifolium subterraneum at different seeding rates (13, 17, 20 kg ha-1) and phenological stages (inflorescence, fruiting). The experiment was conducted in Orestiada, northern Greece under rainfed conditions in 2014. Seeds were sown in February and phosphorus fertilization was applied before the seeding. According to the results agronomic PUE was higher at the inflorescence stage compared to the fruiting one. The lowest value of agronomic PUE was observed at the 17 kg ha-1 seeding rate, while there was no significant difference between the other seeding rates. However, all the corresponding values were negative. Positive agronomic PUE values were recorded at the seeding rate of 13 kg ha-1 during the inflorescence stage and at 20 kg ha-1 during the fruiting stage, indicating that phosphorus fertilization is essential to improve forage yield at the specific seeding rates.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)